Further Investigations into Emission Components of PSR B0950+08 and Correlations between Them with Single Pulses - Jie Liu; Zhen Yan; Hao Tong; Hong-Guang Wang; Zhi-Qiang Shen; Rui Wang; Xiao-Wei Wang; Zhi-Peng Huang (The Astrophysical Journal)
With the phase-to-phase cross-correlation method, we analyzed the single pulses of PSR B0950+08 obtained at the Five-hundred-meter Aperture Spherical radio Telescope. The correlation map produced with the single pulses reveals a modulation of the correlation coefficients, which are between the intensities at different phases of the single pulses. The modulation varies by a period of two phase bins with 2048 bins over the whole pulse phase. Such a modulation is related to the microstructures of the single pulses and may ultimately imply that the Lorentz factors of the charged particles in the pulsar magnetosphere are highly similar along the line of sight trajectory. The modulation rule reverses after a constant phase separation of $191\mathop{.}\limits^{^° }43$ . It also reverses around the peak phase of the mean pulse profile, implying that the Lorentz factors are different from the normal value around the reversal phase. According to the analyses with the correlation map, we propose that the bridge emission between the main pulse (MP) and its preceding interpulse (IP) is the overlap of the MP and the IP. For the “weak emission” trailing the MP, it is identified as an independent profile component. There are strong emissions from the IP but no giant pulse from the MP during this observation. The correlation between the IPs and the MPs is mainly dominated by the positive correlations between the subcomponents of the IP and one subcomponent of the MP, according to our analyses.